Dorset Site Variation on the Southeast Coast of Baffin Island - Maxwell, Moreau S. (ARCTIC, 1980)
The wide variation in Dorset residence structures may indicate seasonal site differences greater than a simple summer/winter dichotomy. This is further suggested by a comparison of selected stone tool frequencies from Dorset sites near Lake Harbour, N.W.T. Here manufacturing activities appear to differ from spring to summer to winter. The evidence also suggests that in this region Late Dorset winter settlements were located on the fast sea ice.